Process hygiene of pig carcasses in one large-scale slaughterhouse in the west of Serbia, during 48 months. (September 2019) - Betic, N; Baltic, T; Ciric, J; Bajcic, A; Raseta, M; Mrdovic, B; Karabasil, N
Abstract: This study was conducted to determine microbial contamination of pig carcasses during four years in one slaughterhouse. The numbers of total viable counts and Enterobacteriaceae and the presence/absence of Salmonella spp. are the process hygiene criteria for pig carcasses. We collected 240 samples from April of 2015 to April of 2019, with swabs being continually taken from the carcasses of pigs every month for 48 months in slaughterhouse in the west of Serbia. Over 48 consecutive months of testing, Salmonella spp. presence was detected on 1.67% of the pig carcasses, while the determined mean numbers of Enterobacteriaceae were 0.18±0.37 log CFU/cm 2, and the mean total viable count of aerobic bacteria was 1.88±0.85 log CFU/cm 2 . The process hygiene criteria results for the tested pig carcasses showed that for total viable count of aerobic bacteria, 95.35% of carcasses fell into the satisfactory process hygiene group, while 4.17% belonged to the acceptable group. Enterobacteriaceae numbers showed 97.90% of the tested pig carcasses belonged to the satisfactory process hygiene group, and 2.10% of carcasses belonged to the acceptable group.